2000
DOI: 10.1159/000021756
|View full text |Cite
|
Sign up to set email alerts
|

Oral Tool Use by Captive Orangutans (Pongo pygmaeus)

Abstract: Eight captive orangutans (Pongo pygmaeus) were given wooden blocks embedded with raisins and bamboo as raw material for tool making in a study of manual laterality. In about three quarters of the raisin extraction bouts, the orangutans held the tool in the lips or teeth rather than in their hands. Three adult males and 2 adult females showed extreme (≥92%) preference for oral tool use, a subadult male and an adult female used oral tools about half the time, and 1 adult female preferred manual tool use. Most or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
2
18
1
1
Order By: Relevance
“…Furthermore, the other primates known to be particularly dexterous-Pan, Papio and Macaca-have the same mean and peak manipulation WS as the general 'primate' pattern (despite large variation in thumb-index proportions and joint mobility), which does not support our hypothesis that these taxa would have higher thumb-index finger manipulation than other primates. Pongo, as predicted, demonstrates a much lower mean and peak thumb-index finger WS compared with all other primates (except Presbytis) for small-and medium-sized objects (R , 0.18), which may help to explain why they often use within-finger grips or the mouth to manipulate objects [24,49] (electronic supplementary material, figure S2). …”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the other primates known to be particularly dexterous-Pan, Papio and Macaca-have the same mean and peak manipulation WS as the general 'primate' pattern (despite large variation in thumb-index proportions and joint mobility), which does not support our hypothesis that these taxa would have higher thumb-index finger manipulation than other primates. Pongo, as predicted, demonstrates a much lower mean and peak thumb-index finger WS compared with all other primates (except Presbytis) for small-and medium-sized objects (R , 0.18), which may help to explain why they often use within-finger grips or the mouth to manipulate objects [24,49] (electronic supplementary material, figure S2). …”
Section: Discussionsupporting
confidence: 54%
“…To date, only a few observations of tool using and manufacturing by wild orangutans have been reported [1,2], even though rehabilitated and captive orang-utans use and manufacture tools frequently [3][4][5]. Here it is reported that wild orang-utans use leaves as a tool to modify their kiss-squeak calls made during agonistic displays.…”
Section: Introductionmentioning
confidence: 80%
“…Interspecific differences in noncommunication orofacial skills might also explain some of the variation in cytoarchitecture. Orang-utans in the wild and captivity, for example, have been noted to exhibit particular facility at manipulating tools with their lips, teeth, and tongue during extractive foraging of insects and seeds [van Schaik et al, 1996;O'Malley and McGrew, 2000].…”
Section: Distinctiveness Of Species-specific Cytoarchitecturementioning
confidence: 99%